Novel triple injection technique - Avante garde for costoclavicular block. A Case series - Priyanka Bansal; Nidhi Sultania (Asian Journal of Medical Sciences, 2024)
Costoclavicular block has garnered the attention of regional anesthesia enthusiasts because the cords are snuggly packed and consistently arranged in a particular pattern around the first part of the axillary artery. The single injection technique has been widely used conventionally, but the effect is unpredictable. The effect is unpredictable because of the septum that compartmentalizes cords in upper and lower compartments. We propose a triple injection technique targeting the individual cords separately. Onset time of sensory block from 16 min to 7 min. The average time for a complete motor block was 9.6 min. The chances of the median nerve sparing, as has been reported in some cases in previous studies, are almost nil by this technique–the corner pocket injection that involves the medial root of the median nerve and the lateral cord that is specifically blocked separately, covering the lateral root of the median nerve. The costoclavicular block has already carved a niche as an excellent choice for surgeries of the upper limb involving the elbow or below the elbow. The use of the triple injection technique makes the block effect more predictable and reliable.